Amides, triterpene and flavonoids from the leaves of Melastoma malabathricum L. - M. Sirat, Hasnah; Darnis, Deny Susanti; Ahmad, Farediah; Takayama, Hiromitsu; Kitajima, Mariko (Springer, 2010)
Successive extraction of the dried leaves of Melastoma malabathricum, followed by purification using repeated chromatographic techniques, yielded six compounds, including two amides, auranamide and patriscabratine, a triterpene, a-amyrin, and three flavonoids, quercitrin, quercetin and kaempferol-3-O-(200,600-di-O-p-trans-coumaroyl)-b-glucoside. Their structures were elucidated by spectroscopic means and also by direct comparison of their spectroscopic data with respective published data. These three phenolic constituents were found to be active as free radical scavengers, with quercetin being the strongest radical scavenger, having an IC50 value of 0.69 lM in the UV method. Quercitrin and kaempferol-3-O-(200,600-di-O-ptrans- coumaroyl)-b-glucoside showed moderate radical scavenging, with IC50 values of 74.1 and 108.8 lM,respectively.